DENTAL AND SKELETAL CHANGES OF THE MAXILLA AFTER RAPID MAXILLARY EXPANSION - A Nocar; M Horáček; T Dostálová; J Trojanová (Czech Dental Chamber, 2022)
Introduction and aim: The aim is to summarize the current literature regarding possible dental and skeletal changes after rapid maxillary expansion (RME). RME is one type of treatment for transverse maxillary anomalies. It is an effective orthodontic treatment procedure in mixed and permanent dentition. It is indicated in patients with transverse dental arch dysplasia. The treated patients are diagnosed with crossbite in the lateral dentition. The goal of treatment is maxillary expansion, which is possible in younger patients due to immature sutures in the maxillary region, especially the palatal suture. The maxillary expansion is mediated by a special orthodontic appliance that is activated periodically. During this treatment, the surrounding structures are also affected and it is therefore advisable to know the limits of the treatment and its effect on the entire perimaxillary complex. In terms of skeletal changes, we focus on transverse, anterior, posterior and vertical changes, palatal suture, nasal cavity, sutures and synchondrosis as well as orbital structures. As an example of dental changes, we consider the change in the position of the molars and the possibility of root and alveolar bone resorption. An example of a commonly used orthodontic appliance for RME is the hyrax. This palatal expander is anchored to the lateral teeth and activated as needed under individually determined conditions. In addition to clinical examination, changes during RME can be monitored by two- dimensional imaging methods such as skull posteroanterior view and teleradiography, and with the development of imaging methods, by three-dimensional X-ray imaging such as cone beam computed tomography (CBCT). Material and methods: The literature search and review focused on rapid maxillary expansion and the changes that accompany it. PubMed, Web of Science, Cochrane, and Scopus databases were used to find literature. The size of the patient cohort, length and method of follow-up, inclusion of a control group, and long-term stability were important for subsequent article selection. Conclusion: RME is a proven orthodontic method to widen the palatal suture in younger individuals. RME treatment affects not only the palatal suture but also the adjacent maxillary structures. In practice, we find the dental changes mainly include a change in the intermolar distance, buccal inclination of the teeth, possible resorption of the tooth root or resorption of the vestibular alveolar bone. Significant skeletal changes are in the nasal cavity, where air passage may be positively affected with a reduction in airway resistance. Other skeletal effects include, for example, changes in the perimaxillary sutures and synchondroses or orbital structures.